2017
DOI: 10.1017/pasa.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Scattering Polarisation of the d-States of Ions and Solar Magnetic Field: Effects of Isotropic Collisions

Abstract: Analysis of solar magnetic fields using observations as well as theoretical interpretations of the scattering polarization is commonly designated as a high priority area of the solar research. The interpretation of the observed polarization raises a serious theoretical challenge to the researchers involved in this field. In fact, realistic interpretations need detailed investigations of the depolarizing role of isotropic collisions with neutral hydrogen.The goal of this paper is to determine new relationships … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Next, we concentrate on the polarization transfer rates D k (J → J ) obtained in the tensorial basis and fundamental for spectro-polarimetric studies where k is the tensorial order. Full details about the D k (J → J ) and the use of the tensorial basis for polarization studies can be found in the papers by [1,[10][11][12]14,28,29,[31][32][33][34][35].…”
Section: Polarization Transfer Rates Of Complex Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we concentrate on the polarization transfer rates D k (J → J ) obtained in the tensorial basis and fundamental for spectro-polarimetric studies where k is the tensorial order. Full details about the D k (J → J ) and the use of the tensorial basis for polarization studies can be found in the papers by [1,[10][11][12]14,28,29,[31][32][33][34][35].…”
Section: Polarization Transfer Rates Of Complex Atomsmentioning
confidence: 99%
“…Let us consider an isotope of an atom with nuclear spin I and the total angular momentum of a hyperfine structure F = J + I. [35] provided a detailed discussion regarding the direct and indirect methods to calculate collisional hyperfine rates.…”
Section: Extension To Atoms With Hyperfine Structurementioning
confidence: 99%